Kompresi Data Berdasarkan Perhitungan Distribusi Probabilitas Kemunculan Karakter Orde Dua Dalam Teks Bahasa Indonesia - Christyono, Yuli (Departemen Teknik Elektro, Universitas Diponegoro, 2008)
In modern world, the need for capacity data storage and electronic data communications channel is important. Capacity storage media and channel communication in electronic data that we use at this time is not unlimited and it is quite expensive.Therefore, we need a method to use electronic data storage and communications resource optimally and efficiently. One effort that can do at this time is to perform data compression. Data will be compressed before store or before send, so that storage capacity of the data after compression is smaller than before and economize time to send data after compression. There are many kind of method which used in data compression.This research will study about the theory of probability, calculate distribution probability of character order two of text in indonesian language, coding based on Huffman theory, and design software for data compression.Keywords: sandi, kompresi, penyandian, huffman, lossy, lossles